Linear correlation between Debye temperature and lattice thermal conductivity in II-VI and III-V semiconductors - Daoud, Salah (International Journal of Scientific World, 2015)
A simple linear empirical relationship between high intrinsic lattice thermal conductivity K, and Debye temperature Î¸a is suggested from data on high intrinsic lattice thermal conductivity K, and Debye temperature Î¸a for some selected II-VI and III-V cubic zincblende type, and I-VII and II-VI rock-salt type binary semiconductors. A good linear correlation between Debye temperature and the high intrinsic lattice thermal conductivity was obtained. The minimum average percentage deviations in the present approach reveal that our simple model prove its identity and soundness compared to those of other author relations.